Indigenous Concepts of ‘Living Systems’: Aristotelian ‘Soul’ meets Constructal Theory - Pierotti, Raymond (Ethnobiology Letters, 2015)
I examine similarities among the ways of thinking concerning the natural world of Indigenous peoples of North America and Australia and two aspects of Western Science from different historical periods. The first comparison is with constructal theory, a set of ideas and models recently developed to explain how ‘design’ arises in both biotic and abiotic systems. Both traditions emphasize the importance of flow and motion and how these generate connections, not only within biotic systems, but also between biotic and abiotic phenomena. The second comparison goes back to the beginnings of the Western scientific tradition, and involves the Aristotelian concept of the ‘soul,’ an entity which is not considered to be supernatural, but more of an emergent property of living systems that also involves flow, especially of heat and air within living systems. Both comparisons reveal that indigenous knowledge is thoroughly scientific, but not in the sense characterized by the Baconian/Cartesian tradition, which is more focused on mechanism and application to human affairs than to understanding how natural systems actually function. Indigenous knowledge focuses more on relationships than on mechanisms, and thus is best compared to Western scholarly traditions that also emphasize relationships and emergent properties.